2016
DOI: 10.3390/nu8010023
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Desaturases, Polyunsaturated Fatty Acid Regulation, and Biotechnological Advances

Abstract: Polyunsaturated fatty acids (PUFAs) are considered to be critical nutrients to regulate human health and development, and numerous fatty acid desaturases play key roles in synthesizing PUFAs. Given the lack of delta-12 and -15 desaturases and the low levels of conversion to PUFAs, humans must consume some omega-3 and omega-6 fatty acids in their diet. Many studies on fatty acid desaturases as well as PUFAs have shown that fatty acid desaturase genes are closely related to different human physiological conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
213
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(220 citation statements)
references
References 100 publications
4
213
0
3
Order By: Relevance
“…S1 (chemical structures), FAs as well as the lipid metabolites analyzed by LC-MS/MS and GC-MS are shown. Figure 1 depicts both conventional and alternative biosynthetic pathways of PUFAs in eukaryotes383940 including a proposed pathway for the production of JuA in gymnosperms41 ( vide infra ). Sequence comparisons of the major enzymes involved in the biosynthesis of AA and/or degradation of ECs did not provide informative molecular phylogenetic relationships (Supplementary Excel File S1).…”
Section: Resultsmentioning
confidence: 99%
“…S1 (chemical structures), FAs as well as the lipid metabolites analyzed by LC-MS/MS and GC-MS are shown. Figure 1 depicts both conventional and alternative biosynthetic pathways of PUFAs in eukaryotes383940 including a proposed pathway for the production of JuA in gymnosperms41 ( vide infra ). Sequence comparisons of the major enzymes involved in the biosynthesis of AA and/or degradation of ECs did not provide informative molecular phylogenetic relationships (Supplementary Excel File S1).…”
Section: Resultsmentioning
confidence: 99%
“…Endogenous biosynthesis of EPA and DHA from ALA requires several desaturation and elongation reactions, with Δ6 and Δ5 desaturases playing key roles. Fatty acid desaturase (Fads) gene clusters encode for enzymes that are critical for the synthesis and regulation of n‐3 PUFA (Lee, Lee, Kang, & Park, ). Missotten, De Smet, Raes, and Doran () reported that n‐3 PUFA enriched diets may indirectly affect carcass fatty acid composition through modification of lipogenic enzyme expression.…”
Section: Discussionmentioning
confidence: 99%
“…These results further evidenced that the evolutionary history of genes involved in the LC-PUFA biosynthetic pathways of invertebrates, particularly the Fads-like desaturases, might differ markedly from those of vertebrates [6,12,19]. Clearly, marine invertebrates emerge as promising sources of LC-PUFA biosynthetic enzymes with potentially novel functionalities amenable for biotechnological production of n–3 oils [20]. …”
Section: Introductionmentioning
confidence: 99%